The field geology and petrography of the kofayi younger granite complex, central Nigeria - T, Aga; A. I, Haruna (International Journal of Advanced Geosciences, 2019)
The Kofayi Younger Granite Complex is one of the several anorogenic alkaline Younger Granite Complexes that is located approximately 45 kilometres north east of Jos, Nigeria. The complex is found to comprise of felsic rocks like; biotite-granites, biotite microgranites and granodiorites. They are also found to be associated with mafic rocks like diorites which, at some portions have formed hybrid rocks. Quartz- feldspar- granites are the porphyritic rocks that found in the ring complex. The complex intrude the basement rocks of central Nigeria. Structural trends on these rocks suggest that they were controlled by some deep seated structures of the basement. Mineral suite identified include; fayalite, pyroxene, amphibole, k-feldspar, biotite, quartz, iron- oxide and accessory minerals like zircon, apatite, and allanite. Generally, the petrography of these rock samples reveal the presence of a mafic magma which has two pulses (a mafic and felsic pulse) of injection.Â